The Influence of Service Quality, Price, and Location on Purchase Intention and Loyalty in Gold Retail SMEs: Pengaruh Kualitas Layanan, Harga, dan Lokasi terhadap Niat Beli dan Loyalitas pada Usaha Mikro, Kecil, dan Menengah (UMKM) Ritel Emas - Sahda, Talitha Sholikhatus; Safirin, Moch. Tutuk (Academia Open, 2026)
General Background Customer loyalty is vital for small and medium enterprises because repeat purchases and recommendations sustain long-term business performance. Specific Background UKM Emas Podo Joyo Gresik experienced declining revenue from 2021 to 2025, indicating weakening purchase intention and customer loyalty in the gold jewelry retail sector. Knowledge Gap Previous studies often examined service quality, price, and location separately, while empirical models integrating these variables with purchase intention and loyalty in gold jewelry SMEs remain limited. Aims This study analyzes the relationships between service quality, price, location, purchase intention, and customer loyalty at UKM Emas Podo Joyo Gresik. Results Using a quantitative survey of 100 respondents who had transacted at least twice and Partial Least Square Structural Equation Modeling with SmartPLS 3, the findings show that service quality had positive and significant relationships with both purchase intention and customer loyalty. Price and location were significant for purchase intention but not significant for customer loyalty. Purchase intention also had a positive and significant relationship with customer loyalty. Novelty This study develops an integrated PLS-SEM model for marketing behavior in a gold jewelry SME context. Implications Business strategy should prioritize better customer service while maintaining competitive pricing and accessible location management to strengthen buying interest and repeat patronage. Highlights: Staff interaction supported buying interest and repeat commitment. Price and location mattered mainly before purchase. Buying interest became a significant pathway to repeat patronage. Keywords: Service Quality, Price, Location, Purchase Intention, Customer Loyalty, PLS-SEM